Tarkasaṅgrahacandrikā : Śrīmadannaṃbhaṭṭakrtatarkasaṅgraha-vyākhyā - Mukundabhaṭṭa, 19th cent (Nirṇayasāgarākhyayantrālaye, 1912)
Sanskrit commentary on Tarkasaṅgraha of Annambhaṭṭa, basic work on the fundamentals of Nyaya and Vaiśeṣika school in Hindu philosophy.